Molecular Dynamics Study of Nanoscratching Behavior of Water-Film-Covered GaN (0001) Surface Using Spherical Diamond Abrasive - Jiaqin Yin; Shuaicheng Feng; Yang Liu; Jian Guo (Crystals)
Molecular dynamics (MD) simulation of nanoscratching with a spherical diamond abrasive was performed to investigate the role of water molecular film on the surface nanotribological characteristics and subsurface lattice damage of GaN (0001) at the atomic level. The simulation results indicate that the tangential and normal forces exhibited no significant variation trend with the increase in water film thickness. Inducing a water film can alleviate the material pile-up during scratching, and the GaN surface obtained the lowest friction coefficient and wear volume when the water film thickness reached 3 nm, primarily due to the enhanced lubrication and the heat absorption by the water film in this case. Water-film-covered GaN exhibited a thinner subsurface damage layer than the bare GaN, and the damage layer thickness decreased with the increase in water film thickness for various scratching depths of 1 to 4 nm. For each scratching depth, there was an optimal water film thickness causing the minimum number of amorphization atoms. Nevertheless, the water film failed to inhibit the formation and propagation of dislocations in the scratching process, and water-film-covered GaN exhibited more dislocations than the bare one. This research has the potential to expand the comprehension of water-mediated nanotribology and the ultra-precision machining procedures of GaN.